Effectiveness of Integrating Focused Listing Formative Assessment in Concept Attainment Models (CAM) Learning in Improving Concept Understanding of High School Students on Sound Waves Material - Nenden Choirun Nisa; Efendi, Ridwan; Aviyanti, Lina (Department of Physics Education, Universitas Mataram, 2025)
Conceptual understanding is an indicator of success in learning. One fundamental concept in physics that plays an important role is sound waves. However, observations, questionnaires, and interviews show that students' conceptual understanding is still low. This condition indicates the need for learning that not only helps students understand concepts but is also equipped with formative assessment to monitor conceptual understanding. One alternative that can be used is the integration of focused listing formative assessment in Concept Attainment Models (CAM) learning to improve students' conceptual understanding. The purpose of this study is to determine the effectiveness of integrating focused listing formative assessment techniques in Concept Attainment Models (CAM) learning in improving high school students' conceptual understanding of sound waves. The research method used is a quasi-experimental design with a nonequivalent control group design. The research sample involved 65 eleventh-grade students at a public high school in Garut Regency, divided into 35 students in the experimental class and 30 students in the control class. Data collection techniques in this study included concept comprehension tests, focused listing formative tests, and surveys in the form of questionnaires. The results of the study indicate that the integration of formative focused listing assessment techniques in CAM learning is effective in improving students' conceptual understanding of sound wave material, with an increase in conceptual understanding of 61.86% and an effect size of 0.709, which falls into the moderate category.